Tempo para o letramento literário: uma proposta de leitura na biblioteca escolar - Teixeira, Ana Claudia Costa de Aquino (2016)
This present research Time for Literary Literacy: a reading proposal to the school library, had as its main objective to observe and analyze the consequences of the pedagogical action of reading literary narratives aloud by a teacher, in the space-time of the school library, set up in a sequence of reading and writing activities, integrated with the Portuguese language teaching. The question that guided this work was structured as follows: What developments can be observed from the reading of literary narratives aloud, performed by a teacher in the school library space-time? In order to reflect on our research object, the reading, theoretical background studies of Kleiman (2006; 2008), Tfouni (1995), Rojo (2010; 2012), Manguel (2004 [1996]), Cosson (2014 [2006]), among others were used. The methodology adopted in this process is centered in the Action-research field and qualitative inquiries, and therefore, interpretation, based on the studies of Tripp (2005), Bogdan (1994). As data collection and production the instruments used were questionnaires, initial diagnostic activities, students textual productions performed during the intervention (first and last) and the researcher reflective diary. The research locus was a public school, set in a suburb, located in Feira de Santana, in Bahia. The study subjects were 22 students enrolled in a 5th grade class of elementary school, seeking to observe the students‘ reader profile at the final cycle of schooling. The results of this research confirmed that the reading aloud performed by a teacher is a pedagogical action that can directly influence the formation of critical and reflective individuals, because the reading of narratives, especially those present in literary texts can help extend significantly self-understanding and world understanding, decisively helping the individual choices in readings and also interfering positively in the students written productions.